Utilization of Psychotherapeutic Interventions by Pediatric Psychosocial Providers - Cynthia Fair (MDPI AG, 2021)
One of the Standards of Psychosocial Care for Children with Cancer and their Families recommends that all youth with cancer and their family members have access to psychotherapeutic interventions and support throughout the cancer trajectory. This study was created to identify the psychosocial interventions and services provided to children with cancer and their family members, to ascertain whether there are differences in interventions provided by age of the patient and stage of treatment, and to learn about barriers to psychosocial service provision. An online survey was disseminated to psychosocial providers through the listservs of national and international professional organizations. The majority of the 242 respondents were either psychologists (39.3%) or social workers (26.9%) and 79.7% worked in the United States. The intervention offered most often to pediatric patients, caregivers, and siblings, at every stage of treatment, was psychoeducation (41.7–48.8%). Evidence-based interventions, including cognitive behavioral therapy (56.6%) and mindfulness-based interventions (57.9%) were reported to be frequently used with patients. Interventions designed specifically for the pediatric oncology population were not commonly endorsed. Psychosocial providers reported quality of care would be improved by additional staff, better communication/collaboration with medical team members and increased community-based resources. Future research should focus on improving accessibility to population-specific evidenced-based interventions and translating science to practice.